Development of An Evaluation Instrument Model for The Counseling Guidance Service Program for Student Discipline - Adam, Muhammad Imanul; Anirusilowati, Anirusilowati; Awalya, Awalya (Journal of Research and Educational Research Evaluation, 2023)
This research aimed to develop disciplinary instruments and student rules using a questionnaire. To achieve this objective, a Research and Development was employed by using an assessment instrument in the form of a questionnaire (non-test). As the subject of this research, small and large scales with 250 students were used by ten development steps. Validation and reliability were simplified into three stages: preliminary, development, and evaluation. The preliminary stage involved determining instrument specifications, writing the instrument, and determining scoring. The development stage involved counseling guidance, trialing, analysis, and revision. The evaluation stage involved assembling and refining the instrument. Validity analysis and content reliability were performed using Aiken's V formula and Crombach's Alpha. Field tests showed that all items on the student discipline and rules instrument had a value of > 0.3, indicating validity and reliability. Whereas if the reliability test is >0.7, the instrument is valid and reliable, so the instrument is suitable for use. The results were in the valid and reliable category with a Likert scale of 4,3, and 2, indicating good rules and discipline among SMA AZ Semarang City students. However, efforts are needed to improve violations of rules and discipline, even if they are minor.